An in vivo pharmacological study: Variation in tissue-accumulation for the drug probucol as the result of targeted microtechnology and matrix-acrylic acid optimization and stabilization techniques - Mooranian, Armin (PLoS One, 2019)
Type 2 diabetes (T2D) is characterised by β-cell damage and hyperglycaemia. The lipophilic drug, probucol, has shown significant β-cell protective and potential antidiabetic effects, which were enhanced by hydrophilic bile acid incorporation using taurocholic acid and chenodeoxycholic acid. However, probucol has severe cardiotoxicity and a variable absorption profile, which limit its potential applications in T2D. Accordingly, this study aimed to design multiple formulations to optimise probucol oral delivery in T2D and test their effects on probucol absorption and accumulation in the heart. Adult male mice were given a high fat diet (HFD), and a week later, injected with a single dose of alloxan to accelerate T2D development, and once diabetes confirmed, divided into three groups (six to seven mice each). The groups were gavaged a daily dose of probucol powder, probucol microcapsules, or probucol-bile acid microcapsules for three months, and euthanized; and blood, tissues, and feces collected for blood glucose and probucol concentration analyses. Probucol concentrations in plasma were similar among all the groups. Groups given probucol microcapsules and probucol-bile acid microcapsules showed significant reduction in probucol accumulation in the heart compared with the group given probucol powder (p<0.05). Probucol microencapsulation with or without bile acids reduced its accumulation in heart tissues, without changing plasma concentrations, which may be beneficial in reducing its cardiotoxicity and optimise its potential applications in T2D.